MINDFULNESS-BASED INTERVENTIONS FOR PERINATAL MATERNAL MENTAL HEALTH: A SYSTEMATIC REVIEW - Ni Nyoman Widiasih; Ni Wayan Armini; Ni Made Dwi Purnamayanti (LLDIKTI Wilayah X, 2026)
Maternal mental health problems during the perinatal period remain a significant global health concern due to their impact on maternal well-being, pregnancy outcomes, and infant development. Mindfulness-based interventions have increasingly been used as non-pharmacological approaches to improve psychological well-being among pregnant and postpartum women. This systematic review aimed to analyze the effectiveness of mindfulness-based interventions for perinatal maternal mental health. The review used a systematic literature review design with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Literature searches were conducted through Google Scholar, ScienceDirect, PubMed, and SpringerLink for articles published from 2021 to April 2026. A total of 13 studies met the inclusion criteria. The reviewed studies mainly consisted of randomized controlled trials evaluating mindfulness counseling, mindfulness-based childbirth and parenting programs, meditation, relaxation techniques, and digital mindfulness interventions. Overall, mindfulness-based interventions demonstrated positive effects in reducing anxiety, depression, stress, pregnancy-related distress, and fear of childbirth. Several studies also reported improvements in emotional well-being, childbirth satisfaction, mindfulness awareness, maternal–fetal attachment, and breastfeeding self-efficacy. Mindfulness-based interventions represent effective complementary approaches for improving perinatal maternal mental health, particularly in reducing psychological distress and enhancing maternal emotional well-being during pregnancy and postpartum.